Menumbuhkan Kesadaran Anti-Bullying pada Siswa SD Negeri Kedungsari 3 melalui Edukasi dan Sosialisasi - Zahro, Sayyidah Khoirul; Saputra, Nafis Ghalib; Septiana, Palupi; Maulidina, Farhana Rizqi; Putri, Listiana Ayu; Nugraha, Joko Tri (Universitas Pahlawan Tuanku Tambusai, 2026)
Bullying remains a serious problem in schools because it can negatively impact students' mental and physical health. This phenomenon is often found in elementary school-aged children who are at a vulnerable stage of social and emotional development. This community service activity aims to increase the understanding and awareness of students at Kedungsari 3 Elementary School, North Magelang, regarding the importance of bullying prevention through outreach activities. The outreach was conducted using an interactive approach through the delivery of material using illustrated presentations and animated videos to facilitate student understanding. To measure the effectiveness of the activity, pre- and post-tests were conducted on 27 sixth-grade students to determine their level of understanding. The evaluation results showed a significant increase, with the average student score increasing from 50 in the pre-test to 90 in the post-test. In addition, students demonstrated active participation throughout the entire series of activities. Thus, interactive outreach based on audio-visual media has proven effective in fostering understanding and awareness regarding bullying prevention in elementary schools.